Efeito da adubação e poda sob o cultivo de Hibiscus sabdariffa L. - Araujo, Wallyson Santos (2020)
The use of unconventional food plants can become a great alternative as a nutritional and functional source for human consumption. Considering the need to improve the yield of unconventional plants, with increased productivity without increasing the production area, the objective of the present work was to cultivate the species Hibiscus sabdariffa L, to evaluate the growth and physiological development of plants under different types of fertilization and pruning. The experiment was carried out in the field, in randomized blocks, with three replications, using a 4x2 factorial scheme, four types of fertilization (control, chemical, organic and mixed), and two forms of management (with pruning and without pruning). Physiological assessments were carried out using the Pocket - PEA fluorimeter, portable chlorophyll meter, model SPAD-502 and biometric assessments. At 50 DAP, plants that received fertilization showed higher averages for green intensity and for the photosynthetic index, differing from the control treatment. Fertilization and pruning did not influence the physiological parameters in the other days of evaluation. The data of plant height, stem diameter and leaf width, showed linear growth and chemical and mixed fertilization, were higher for number of commercial branches, fresh weight of commercial branches, total fresh weight and dry weight of leaves. The treatments that received chemical and mixed fertilization presented better performances in the growth parameters of Hibiscus sabdariffa L. and associated with the use of pruning, favored the production of aerial biomass. Given their superior responses, it is reasonable to recommend the use of these techniques in the cultivation of this species to obtain better performances in the production of commercial branches.